Kepemimpinan Kreatif dalam Menciptakan Disrupsi Pasar: Bagaimana Pemimpin Mendobrak Pasar dengan Model Bisnis Baru - Irsyad Ilham; Ine Nova Ayu; Siti Hanifatu Sya’adah; Yusriyah Yunita; Nabila Kania Zahra (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Technological shifts and changing consumer behaviors require organizations to continuously innovate in order to remain competitive. In this context, creative leadership plays a strategic role in driving market disruption through the development of relevant and adaptive business model innovations. This study adopts a qualitative approach based on secondary data using the Systematic Literature Review (SLR) method. A variety of academic sources, including journal articles and case studies of companies such as Netflix, Gojek, and Ruangguru, were systematically analyzed to identify strategic leadership patterns in creating disruption. The findings indicate that creative leaders do more than just adopt technology—they design innovation ecosystems that foster experimentation, continuous learning, and responsiveness to market needs. Strategies such as digital platform development, big data utilization, and business model transformation serve as key tools in challenging conventional market boundaries. This study contributes conceptually to the understanding of the relationship between creative leadership and business model innovation in navigating the complexities of the digital era.